2018
DOI: 10.1108/jaee-08-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social, environmental and corporate governance disclosures on firm value

Abstract: Purpose The purpose of this paper is to examine the impact of environmental, social, and governance (ESG) practices disclosure and firm value in the Egyptian context. This is done through investigating the influence of being listed and ranked in the Egyptian Corporate Responsibility Index on firm value during the period starting from 2007 to 2016. Design/methodology/approach Using univariate and multivariate analyses, the findings support the economic benefits of ESG disclosures. Findings The authors find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
137
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(207 citation statements)
references
References 82 publications
(152 reference statements)
11
137
2
4
Order By: Relevance
“…This study finds a positive association of environmental and social performance with the financial performance of banks in emerging countries. Previous studies also found a positive association of environmental and social performance with financial performance in the company level (Aboud & Diab, 2018;Velte, 2017) and bank level (Buallay, 2019;Esteban-Sanchez et al, 2017). The positive link may occur due to stakeholders' interest in the company or bank ESG disclosure.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This study finds a positive association of environmental and social performance with the financial performance of banks in emerging countries. Previous studies also found a positive association of environmental and social performance with financial performance in the company level (Aboud & Diab, 2018;Velte, 2017) and bank level (Buallay, 2019;Esteban-Sanchez et al, 2017). The positive link may occur due to stakeholders' interest in the company or bank ESG disclosure.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies found a strong relationship with good corporate governance and CSR practices of the company (Aboud & Diab, 2018;Kaymak & Bektas, 2017). Strong corporate governance may influence the financial performance of banks.…”
Section: Governance Performance and Financial Performancementioning
confidence: 92%
See 2 more Smart Citations
“…Their study brought no significant conclusions establishing a relationship between the variables. ESG was once again explored by Ferrero‐Ferrero, Fernández‐Izquierdo, and Muñoz‐Torres () who sought to explore the effects of ESG consistency on economic performance; Aboud and Diab () who found a positive relationship between ESG quality and firm value; Atan, Alam, Said, and Zamri () who found no relationships for the selected sample; Zhao et al () who analyzed power generation companies; and Xie, Nozawa, Yagi, Fujii, and Managi () who showed that most ESG activities have a nonnegative relationship with financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%